TINDAKAN PENGANCAMAN WAJAH DAN STRATEGI KESOPANAN PADA KOMUNIKASI MASYARAKAT DI SINGARAJA-BALI - I Gusti Ayu Vina Widiadnya Putri; Wayan Nurita (Universitas Sebelas Maret, 2021)
This research was conducted to determine Face-threatening Act and the politeness strategies used by the community in daily communication. There is another intention or meaning behind the speaker's speech.. Therefore, pragmatic studies can determine and analyze this language study. The politeness strategy is a pragmatic study conducted to respect the interlocutor in communication. Face threatening is an act that threatens a person's face. Any face threatening that occurs regularly in daily interactions is often proposed and justified by politeness. Data in this study are the interaction of the Singaraja community. Data in this interaction are collected and analyzed qualitatively based on a theory proposed by Brown and Levinson (1987) about Face-threatening Act which is often abbreviated as FTA. Based on the results of data analysis shows that there are two types of face threatening act found, namely: Positive Face-threatening Act and Negative Face-threatening Act. In carrying out, four politeness strategies were found in social interaction, namely; First, do the FTA directly (on record); Second, do the FTA indirectly (off record); Third, use a positive politeness strategy, and Fourth use a negative politeness strategy.